BERTAHANNYA BANGSAWAN BONE DI TENGAH PERUBAHAN REZIM, 1811-1946 - Mappangara, Suryadi (Masyarakat Indonesia, 2011)
The implementation of the autonomy Law in the early 2001 in Indonesia has lead to the emergence of petty kings in several regions. However, the diversity of the local political history will be inﬂuenced or inﬂuence the ways in which regional autonomy are practiced by local elites. By taking the political history of Bone from 1811 to 1946 as a case study, this dissertation shows that the current petty kings have long been maintained by decendants of aristocratic elite in Bone. There are three interrelated factors that make the aristocrats in Bone are able to survive in maintaining their power until now; namely political marriages, social networks, and patron-client relationship. The colonial government failed to understand three important factors embedded in the long political history of Bone. This lack of knowledge about history and political culture of Bone has led to ongoing conﬂict between Bone’s aristocrats and the colonial government. By using local sources,Lontara and colonial sources, the dissertation attempts to provide balanced analysis of the dynamics of local political structures of Bone from the period 1811 to 1946.